O debate sobre as finalidades da escola em parte da produção científica nacional - de 2014 a 2024 - Scherer, Fabiana (2024)
The study aimed to present and discuss part of the contemporary academic-scientific production on the purposes of public basic education schools, with emphasis on studies published between 2014 and 2024, or the period of formal validity of Law 13.005/2014 - Plan National Education. Methodologically, this is a meta-research, which focused on part of the academic-scientific production regarding the purposes of public basic education schools, preparing a bibliographical survey and referencing publications in this regard in periodicals, theses and dissertations. Given the empirical corpus constituted, the following themes were present in academic-scientific productions: socialization; democratic school, management and citizenship, cultural space in all its contexts; school as an environment that prepares you for life and work; challenges facing the school and its agents for human training and development; protective space for rights; construction of identity and space for the appropriation of culture and knowledge; transmission of content, reception and care, integral training of the person, training for work, training of citizens, training for life and society and social transformation; the school as a socially recognizable physical space of transformation, and the relationship between the family and the school configuration. The research concluded, based on the production examined, that the purposes of the public basic education school in the time frame examined were treated, by the academic-scientific production, based on a multidimensionality of biases and readings, but highlighting the importance of the institution for the social constitution.